2020
DOI: 10.1021/acscatal.0c01789
|View full text |Cite
|
Sign up to set email alerts
|

Engineered PQQ-Dependent Alcohol Dehydrogenase for the Oxidation of 5-(Hydroxymethyl)furoic Acid

Abstract: Furan-2,5-dicarboxylic acid (FDCA) is a bio-based platform chemical with the potential to replace terephthalic acid in the production of polymers. A critical step for enzymatic and whole-cell production of FDCA from 5-(hydroxymethyl)­furfural (HMF) is the transformation of 5-(hydroxymethyl)­furoic acid (HMFA) into 5-formylfuroic acid (FFA). Here, we establish periplasmic pyrroloquinoline quinone (PQQ)-dependent alcohol dehydrogenases (ADHs) as biocatalytic tools for the oxidation of HMFA, HMF, and 5-formylfurf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Because of the ring-shaped structure of FAL, a steric hindrance would be formed when it combined with the activity site of the enzymes. In previous research, although the ADH was confirmed to have high activity of the CO bonds, the high selectivity of furan alcohols can be achieved by whole-cell catalysts with overexpressed ADH . Nevertheless, the binding state of FAL in ADH remained unclear.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Because of the ring-shaped structure of FAL, a steric hindrance would be formed when it combined with the activity site of the enzymes. In previous research, although the ADH was confirmed to have high activity of the CO bonds, the high selectivity of furan alcohols can be achieved by whole-cell catalysts with overexpressed ADH . Nevertheless, the binding state of FAL in ADH remained unclear.…”
Section: Resultsmentioning
confidence: 98%
“…In previous research, although the ADH was confirmed to have high activity of the CO bonds, the high selectivity of furan alcohols can be achieved by whole-cell catalysts with overexpressed ADH. 53 Nevertheless, the binding state of FAL in ADH remained unclear. In this section, to better understand the mechanism of the visible light-driven biocatalysis process, molecular docking simulation was carried out to confirm the binding between FAL and ADH.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, proteins of the ped cluster have been shown to be involved in the oxidation of alcohols by P. putida KT2440 (Bator, Karmainski, et al, 2020; Li et al, 2020; Thompson et al, 2020). Subsequently, using cytochrome c , electrons are transferred to the cytochrome c oxidase (PP_2675, PedF), which was also less abundant here, in turn reducing O 2 as part of the respiratory electron transfer chain (García‐Horsman et al, 1994; Wehrmann et al, 2020). The downregulation of the ped can thus be reasoned with the temporary low abundance of molecular O 2 , impeding the functionality of PedF and potentially the PQQ biosynthesis pathway, which requires molecular O 2 itself.…”
Section: Discussionmentioning
confidence: 99%
“…GO M 3–5 was reported to rapidly oxidize 50 mM HMFCA to FFCA within 1 h in the presence of HRP and CAT, although Dd GO displayed low catalytic activity toward HMFCA . A periplasmic PQQ-dependent ADH from P. putida KT2440 (PedH) was engineered to oxidize HMFCA to FFCA . The wild-type (WT) enzyme showed no activity toward HMFCA, while the variant F412 V/W561A had the specific activity of about 1 U/mg.…”
Section: Catalytic Oxidationmentioning
confidence: 99%